Halofuginone and artemisinin synergistically arrest cancer cells at the G1/G0 phase by upregulating p21(Cip1) and p27(Kip1) - Chen, Guoqing (Oncotarget, 2016)
Combinational drug therapy is one of the most promising strategies in modern anticancer research. Traditional Chinese medicine (TCM) formulas represent a wealth of complex combinations proven successful over centuries of clinical application. One such formula used to treat a variety of diseases, including cancer, contains two herbs, whose main active components are Halofuginone (HF) and Artemisinin (ATS). Here we studied the anticancer synergism of HF and ATS in various cancer cell lines and in a xenograft nude mice model. We found that the HF-ATS combination arrested more cells at the G1/G0 phase than either one alone, with the concomitant increased levels of CDK2 inhibitors, p21(Cip1) and p27(Kip1). By knocking down p21(Cip1) and p27(Kip1) separately or simultaneously in HCT116 cells and MCF-7 cells, we found that p21(Cip1) was required for HF induced G1/G0 arrest, whereas p21(Cip1) and p27(Kip1) were both required for ATS or HF-ATS combination-mediated cell cycle arrest. Moreover, HF-ATS combination synergistically inhibited tumor growth in xenograft nude mice, and this was associated with the increased levels of p21(Cip1) and p27(Kip1). Collectively, these data indicate that the upregulation of p21(Cip1) and p27(Kip1) contributes to the synergistic anticancer effect of the HF-ATS combination.